Precious Nonsense : The Gettysburg Address, Ben Jonson's Epitaphs on His Children, and Twelfth Night. - Booth, Stephen (Berkeley : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1998.
Description based upon print version of record.
JSTOR
Keywords: Shakespeare, William, -- 1564-1616.; Lincoln, Abraham, -- 1809-1865.; Jonson, Ben, -- 1573?-1637.; Jonson, Ben, -- 1573?-1637.; Gettysburg address (Lincoln, Abraham); Twelfth night (Shakespeare, William); English literature -- Early modern, 1500-1700 -- History and criticism; Nonsense literature, English -- History and criticism; Littérature nonsensique anglaise -- Histoire et critique; English literature -- Early modern; Nonsense literature, English; 1500-1700; Criticism, interpretation, etc